(3GdeaGJjM GdYTQI ddfLGMs - (3Gdabj, EHQGgjes; (3aQjO, NGdOs; (3ceGd, Sdhis; (3ceGd, aNQjs ((3GdbGgQIs (3GdeQcR GdcfOj ddJfejI GdHTQjIs, 2000)
(3gPG GdcJGH jCNPc Edi GcJTGaGJ jQTOc ajgG Edi GdWQjbI GdJj JUHM HgG eJMeSG aj GdMGd h jchf dOjc GdNWI GdJj Jecfc ef GdGMJaGX HgPG GdMeGS h JeOc HGdWGbI GdeJCLLI aj Cj dMXI, h SJJYde CSQGQ bhI GdCdJRGe h GdJacjQ GdEjLGHj h GdJUhQ h cja JSJWjY GSJNOGege aj MjGJc GdjhejI dJHdZ GdOQLI GdbUhi ef GdfLGMs
(3GdeMJhjGJ (B: (3GcJTa CSQGQ GdOhGaY GdOGNdjI (B- - (3JYQa Ydi CSQGQ GdWGbI GdHTQjI (B- - (3JYde GSJQGJjLjI GdegGQGJ GdPGJjI (B- - (3hcja JMbb CgOGa MjGJc(B.. (3GdBfs
1 2 4 6 9 11 12 13
Keywords: (3GdgfOSI GdHTQjI (B2s; (3Yde GdfaS GdJWHjbj (B2s